IMPLEMENTASI NILAI MORAL NOVEL KUBAH KARYA AHMAD TOHARI DALAM PEMBELAJARAN - Nasim Taha (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aims to describe the form of moral values, story elements used to convey moral values ​​and techniques for conveying moral values ​​in the novel Dome by Ahmad Tohari published by Gramedia Pustaka Utama. This understanding is focused on problems related to the form of moral values, story elements used to convey moral values ​​and techniques for delivering moral values.Data collection techniques were carried out by reading and recording data points and analyzed by qualitative analysis techniques using content analysis methods. The validity of the data is done by semantic validity, while the reliability of the data is interrater reliability and interrater reliability.The results of the study are described as follows. The first point is the manifestation of moral values ​​in the novel Dome by Ahmad Tohari in the form of human relationships with God, namely belief in God, being grateful to God, and offering prayers. Human relationship with oneself, which is firm in stance, optimism, and completion.Human relations with other humans in the scope of the social environment, namely caring for others, being grateful, respecting others, seven, being patient, and helping each other. The two elements of the story that are used as a means to convey moral values ​​in the novel by Ahmad Tohari are characterizations